مدى فاعلية آليات حوكمة الشركات في قانون النشاط التجاري الليبي رقم (23) لسنة 2010 دراسة مقارنة - أنس عبد القادر عامر (Scientific Journal of University of Benghazi, 2021)
This a Comparative study aimed to determine and show the inefficiency in Effectiveness of Corporate Governance Mechanisms (General Assembly, Board of Directors, External auditor) in Libyan Commercial Activity Act No (23) of 2010 compare with Corporations Laws in both of Egypt and Jordan , then study issued suggestions and requirement adjusts on Libyan Commercial Activity Act No (23) 2010 should make by Libyan’s regulator to enforce Effectiveness of Corporate Governance Mechanisms in Libyan Commercial Activity Act No (23) of 2010, Accordingly, the study recommended that the Libyan legislator guarantee the rights of shareholders through the General Assembly, as well as the necessity of determining the number of members, the number of meetings, salaries and benefits of the board of directors, and ensuring that the work of the external